Analysis of River Flow Velocity Using Current Meter with Six-Tenths Method and Two-Point Method (Case Study of Ampal River, Balikpapan City) - Giarto, Rahmat Bangun; Kiptiah, Mariatul; Pradana, Ryan (International Journal of Research in Vocational Studies (IJRVOCAS), 2023)
Rivers have cross-sectional sizes in the form of longitudinal profiles, valley slopes, and cross sections. The size can change according to the base material, cliffs, and water discharge so each river has different characteristics. The flow velocity will affect the flow rate. This study aims to determine the flow velocity of the Ampal River and determine the differences between the methods used. Measurement of flow velocity in this study using a current meter with the six-tenths method and the two-point method. The fastest flow velocity obtained on average is at the point z/b = 0.5 or in the middle of the river, with the maximum speed being at Cross Section 4, with a depth of 1.29 m and a speed of 0.474 m/s.